Books are for eating - Walton, Sherry; Westcott, Nadine Bernard (New York : Dutton, 1989)
Little Katy is sure her own behavior as a baby was never so appalling as her baby brother$1 (Bs--well, most of the time, anyway.s
D., unk., 6/1997
Keywords: Babies -- Fiction; Brothers and sisters -- Fiction